1947
DOI: 10.1037/h0055789
|View full text |Cite
|
Sign up to set email alerts
|

Differential test responses of normals and mental defectives.

Abstract: Ai assumption is implicit in much of the work of clinicians who diagnose mental deficiency that the behavior of mentally deficient subjects is different qualitatively from that of normal subjects of like mental age. Ordinarily this assumption rests upon the informal observation that certain items on standardized scales of intelligence are either less difficult or more difficult for defectives than for normal subjects of equal mental level. The defective is generally considered to be superior in items depending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

1950
1950
1988
1988

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…Even though the groups were comparable in MA, the factors which go to make up the normals' MA scores may differ from those which make up the Mongoloids' MA scores. A study by Thompson and Magaret (1947) supports such an explanation. These investigators, studying differential test responses of normals and mental defectives on the Revised Stanforcl-Binet, Form L, found that the items which were more difficult for defectives than for normals of equal MA were those which are more heavily saturated with the common first factor extracted by Mc-Nemar.…”
Section: Discussionmentioning
confidence: 89%
“…Even though the groups were comparable in MA, the factors which go to make up the normals' MA scores may differ from those which make up the Mongoloids' MA scores. A study by Thompson and Magaret (1947) supports such an explanation. These investigators, studying differential test responses of normals and mental defectives on the Revised Stanforcl-Binet, Form L, found that the items which were more difficult for defectives than for normals of equal MA were those which are more heavily saturated with the common first factor extracted by Mc-Nemar.…”
Section: Discussionmentioning
confidence: 89%
“…300) dence showing a close parallel between longterm memory and intelligence is rare. Sarason (1952, p. 69) points out that of the 20 items in the Binet test, in which according to Thompson and Magaret (1947) normals surpassed defectives, 8 involved memory. He concludes, however, that as fear and anxiety adversely affect performance on memory items, such items cannot be relied upon as a valid indication of intellectual capacity.…”
mentioning
confidence: 99%
“…One line of research that might enhance our knowledge and diminish our disappointments is to make a distinction between levels of giftedness, for example, the level of giftedness that allows some to graduate from college and the level of exceptional giftedness that aids some to graduate from college and complete other preparatory experiences while in their teens or early twenties. Such distinctions would balance the discriminations made on the lower end of the intelligence continuum (Kebbon, 1965;Matthews, 1963;Sloan & Birch, 1955;Taylor, 1964;Thompson & Margaret, 1947), with liner discriminations at the upper end. While at best suggestive, there are data pointing to achievement and professional differences among subjects at different levels of giftedness (e.g., Albert & Barton, 1969;Fowler, 1962;Frierson, 1965;Gallagher & Lucito, 1961;Getzels & Jackson, 1962;Hildreth, 1954;Hollingworth & Cobb, 1928;Lucito & Gallagher, 1960).…”
Section: Discussionmentioning
confidence: 99%